1991
DOI: 10.1177/1532673x9101900207
|View full text |Cite
|
Sign up to set email alerts
|

Policy Entrepreneurs, Policy Opportunists, and Legislative Effectiveness

Abstract: Although there is a growing literature on policy entrepreneurs and policy enactment, there has been little systematic examination of legislative policy entrepreneurs and the effect of policy entrepreneurship on a legislator's standing. This article identifies policy entrepreneurs in each of three sessions of the North Carolina General Assembly and examines the effect of policy entrepreneurship on legislators' effectiveness as perceived by peers and close observers. It also defines and identifies a second categ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(63 citation statements)
references
References 7 publications
3
56
0
1
Order By: Relevance
“…The important role of individuals in advancing policy change has also been emphasized at the level of international policies, for example, in comprehensive studies on the influence of the lead executive officers of international organizations (Biermann and Siebenhüner 2009). Since the early 1980s, this topic has received attention from various policy scientists (see, e.g., Kingdon 1984, King and Roberts 1987, Weissert 1991, Baumgartner and Jones 1993, who have shown that there is room for individual actors to help stimulate or redirect debate about policy issues. Building and synthesizing upon this work, scholars have given increasing attention to policy entrepreneurs (see, e.g., Young 1991, Schiller 1995, Schneider et al 1995, Mintrom and Vergari 1996, 1998, Mintrom 2000.…”
Section: Introductionmentioning
confidence: 99%
“…The important role of individuals in advancing policy change has also been emphasized at the level of international policies, for example, in comprehensive studies on the influence of the lead executive officers of international organizations (Biermann and Siebenhüner 2009). Since the early 1980s, this topic has received attention from various policy scientists (see, e.g., Kingdon 1984, King and Roberts 1987, Weissert 1991, Baumgartner and Jones 1993, who have shown that there is room for individual actors to help stimulate or redirect debate about policy issues. Building and synthesizing upon this work, scholars have given increasing attention to policy entrepreneurs (see, e.g., Young 1991, Schiller 1995, Schneider et al 1995, Mintrom and Vergari 1996, 1998, Mintrom 2000.…”
Section: Introductionmentioning
confidence: 99%
“…Characteristics such as rationality, the ability to see new possibilities offered by the evolving historical situation and a desire to 'make a difference' are also seen as important (Doig and Hargrove 1987). Weissert (1991) suggests that they do so by raising awareness of issues and moving them from incubation to enactment. Engaging in dissemination and demonstration activities, collaboration with elites and gaining media attention are also facets of entrepreneurship suggested by Roberts and King (1991).…”
Section: Subnational Climate Entrepreneurshipmentioning
confidence: 99%
“…The development or 'invention' of AB32 and Law 13,798 can be understood as 'inherently disruptive processes' (Jordan and Huitema 2014a, p. 718) in their respective territories. These two acts were sponsored by civil society organisations to get them on the legislative roster-moving them from incubation to enactment (following Weissert 1991). Both received bi-partisan support and both deliver medium-term goals, which will be realised several electoral cycles into the future.…”
Section: Establishing Ambitious Legislation and Action Plans (Invention)mentioning
confidence: 99%
“…Others are outside of government. With regard to the former, Weissert (1991), Schiller (1995), and Carter and Scott (2010) focused upon legislators as entrepreneurs. Ness (2008) found that legislative leaders from both the state house and senate in New Mexico used their connections to enact merit aid legislation.…”
Section: The Role Of Public Entrepreneurs In the Diffusion Of Innovatmentioning
confidence: 99%